Konsep Mati (Al-Mawt) Menurut Perspektif Ali bin Abi Talib (R.A.) - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 2004)
This brief paper attempts to give insight into the meaning of al-Mawt from the view point of Ali Ibn Abi Talib (r.a) especially with regard to the concept of al-Mawt itself, the purpose of al-Mawt and al-Mawt as a purification process.